Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2019)
Contents: Comparison between two swing-up algorithms: partial feedback linear and energy based method; fault localization on the transmission lines be wavelet technique combined radial basis function neural network; design of an inclined weight measurement system for prosthetic arm innovation;....